Human rights protection and national interest : the case of border fences in the European Union - Ferrario, Ljuba (2017)
Ever since the beginning of the refugee crisis, the efficiency of the Common European Asylum System has been questioned by MSs and European institutions. Recently, physical barriers have been built by an increasing number of countries in the European Union for the purpose of border controls. Simultaneously, several human rights organization have expressed their concerns on the violation of the right to asylum and of the prohibition of inhuman and degrading treatment resulting from the adoption of this method. This research will analyze this phenomenon through the perspective of international relations theory. The analysis will consider the realist approach in opposition to the liberal one, trying to assess whether border fences can be defined as an expression of national interest which compromises international cooperation in the field of human rights.